Pengaruh Pengetahuan Perpajakan dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor dengan Kesadaran Wajib Pajak Sebagai Variabel Intervening: Studi Kasus pada SAMSAT Kota Gorontalo - Nur’Ain Husa; Nilawaty Yusuf; Muliyani Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to prove the effect of tax knowledge and tax sanctions on taxpayer compliance in paying motor vehicle tax with taxpayer awareness as an intervening variable in Samsat Gorontalo City. This study used primary data, namely by distributing questionnaires to taxpayers registered at Samsat Kota Gorontalo. Sample determination in this study used incidental sampling method. . The number of taxpayers in this study was 100 taxpayers. The method used in this study is Partial Least Square (PLS) using SmartPLS 3.0 data analysis application. The results of this study show that taxation knowledge has a positive effect on taxpayer compliance. Tax sanctions do not have a positive effect on taxpayer compliance. Knowledge of taxation has a positive effect on taxpayer awareness. Tax sanctions have a positive effect on taxpayer awareness. Taxation knowledge positively affects taxpayer compliance with taxpayer awareness as an intervening variable. Tax sanctions positively affect taxpayer compliance with taxpayer awareness as an intervening variable.